Beyond the 'Field of Dreams' model in smallholder forestry: Building viable timber value chains for smallholder tree growers in developing countries. (September 2022) - Carias, Dora; Page, Tony; Smith, Hilary; Race, Digby; Keenan, Rodney J.; Palmer, Graeme; Baynes, Jack
Abstract: Many smallholder tree growers in developing countries and those advising them, hold a view that if they plant trees a market will materialize when the time is right. However, despite strong international demand for timber and potential for smallholders to supply this demand, this 'Field of Dreams' approach, i.e. if you grow it, buyers will come, is not generally a sound strategy. In this study, we aimed to identify the conditions that enable the development of viable timber value chains around smallholder tree growers in developing countries. We reviewed literature on the integration of small-scale producers into value chains, smallholder tree growing, and smallholder commercial forestry to identify conditions, and used four case studies in the Asia-Pacific Region to understand how these influence outcomes for smallholder tree growers in different settings. This analysis provided a basis for recommendations for policymakers and advising agencies on how to support timber value chains for smallholder tree growers. These included deeper understanding of biophysical suitability of locations for tree growing, smallholder capabilities and interests, and provision of clear land tenure, infrastructure, and streamlined regulations sympathetic to smallscale timber operations. Tree growing can generate financial value for smallholders in regions with high human population density, quality road networks and proximity to processing markets and ports. Careful policy design is required to make it 'fit for purpose' at local levels, as conditions vary widely even within a single country. This can identify catalytic interventions and work with existing or near-term market drivers and simplified regulations in the value chain to generate benefits for smallholders. Highlights: Smallholder tree planting must target specific end uses. Adequate planning is essential to develop timber value chains for smallholders. Within one country, conditions for developing viable timber value chains will vary. Some regions display better characteristics for commercial utilization of woodlots. Policies to promote tree growing must be targeted to the specific regional context.